Haemodynamic and structural correlates of the first and second heart sounds in pulmonary arterial hypertension: an acoustic cardiography cohort study. Issue 4 (8th April 2013) - Chan, William; Woldeyohannes, Maryam; Colman, Rebecca; Arand, Patti; Michaels, Andrew D; Parker, John D; Granton, John T; Mak, Susanna
Abstract : Objective: To examine the relationship between acoustic characteristics of the first and second heart sounds (S1 and S2) and underlying cardiac structure and haemodynamics in patients with isolated pulmonary arterial hypertension (PAH) and controls. Design: Prospective multicentre cohort study. Setting: Tertiary referral and community hospitals. Participants: We prospectively evaluated 40 PAH patients undergoing right-heart catheterisation with contemporaneous digital acoustic cardiography (intensity and complexity) and two-dimensional transthoracic echocardiography. To normalise for differences in body habitus, acoustic variables were also expressed as a ratio (S2/S1). 130 participants (55 also had haemodynamic and/or echocardiographic assessment) without clinical or haemodynamic evidence of PAH or congestive heart failure acted as controls. Results: Patients with PAH had higher mean pulmonary artery pressure (mPA; 40±13 vs 16±4 mm Hg, p<0.0001) and pulmonary vascular resistance (9±6 vs 1±1 Wood Units, p<0.0001) compared with controls, but cardiac index and mean pulmonary capillary wedge pressure were similar. More PAH patients had evidence of right ventricular (RV) dilation (50% vs 19%) and RV systolic dysfunction (41% vs 9%) in the moderate–severe range (all p<0.05). Compared with controls, the acoustic profiles of PAH patients were characterised by increased S2 complexity, S2/S1 complexity and S2/S1 intensity (all p<0.05). In the PAH cohort, S2 complexity was inversely related to S1 complexity. mPA was the only independent multivariate predictor of S2 complexity. The severity of RV enlargement and systolic impairment had reciprocal effects on the complexity of S2 (increased) and S1 (decreased). Decreased S1 complexity was also related to evidence of a small left ventricular cavity. Conclusions: Acoustic characteristics of both S1 and S2 are related to the severity of PAH and are associated with RV enlargement and systolic dysfunction. The reciprocal relationship between S2 and S1 complexity may also reflect the underlying ventricular interaction associated with PAH.